(untitled) (Eurasian Journal of Philology Science and Education, 2026)
The article is devoted to the analysis of changes in the official style in modern Kazakh media texts, in particular in the news genre. The study aims to identify the linguistic changes that occur in the structure and style of news texts under the influence of the processes of digitization and convergence of official and conversational discourses. The author considers the main features of the official style in the media text, for example, traces the trends of normativity, cliché, formality and their revision in the context of modern communication. In the Kazakh news discourse, special attention is paid to the appearance of speech elements, expressiveness, as well as anglicisms and internet slang. The official style was traditionally used to create strictly formalized texts (laws, regulations, official statements). However, in the modern media environment, it undergoes changes, becomes democratic, accessible to a wide audience, often combining elements of speech, emotionality and visual material. The topic is timely, given how quickly the forms and methods of communication in the field of media and information exchange change. In recent years, in the context of modern media, there has been a significant change in traditional speech styles, including formal ones, which quickly adapt to the requirements of perception and a wide audience. The conclusions of the article allow us to talk about the formation of a new hybrid style that combines formal and informal features that reflect the change in the socio-cultural role of the media in Kazakh society. The study used methods of descriptive, content analysis, comparative, discourse analysis. Keywords: transformation, media text, cliché, normativity, internet jargon.